CCR5 gene editing and HIV immunotherapy: current understandings, challenges, and future directions - Wang, Jia-Wen; Liu, Jia-Hui; Xun, Jian-Jun (Frontiers in Immunology, 2025)
Human immunodeficiency virus (HIV) infection remains a major global public health challenge. Although highly active antiretroviral therapy (HAART or ART) can effectively control viral replication, it fails to eradicate latent viral reservoirs and poses limitations such as lifelong medication and cumulative drug toxicity. This study focuses on the pivotal role of C-C chemokine receptor 5 (CCR5) gene editing in HIV immunotherapy, particularly highlighting the natural resistance to R5-tropic HIV strains observed in the “Berlin” and “London” patients carrying the homozygous CCR5-Δ32 mutation. We further explore the synergistic potential of multiplex gene editing strategies—including CCR5, CXCR4, and HIV LTR loci—and the combinatorial mechanisms between gene editing technologies and immunotherapy. A personalized treatment framework is proposed to address the clinical heterogeneity among people living with HIV. In addition, we assess the balance between long-term safety and global accessibility of gene-editing approaches such as CRISPR/Cas9, emphasizing strategies to enhance therapeutic efficacy while reducing cost and off-target effects. Our findings suggest that the integration of CCR5-targeted gene editing with immune-based interventions holds great promise for overcoming current therapeutic limitations and achieving functional HIV cure. However, key challenges—such as immune rejection, viral tropism switching, and economic feasibility—must be resolved. This integrative approach provides a robust theoretical and technical foundation for the next generation of HIV treatment paradigms.